Myocardial ischaemia of non-obstructive origin as a cause of new onset anginal chest pain in the long COVID syndrome. (14th October 2021) - Espejo, C; Mejia-Renteria, H; Travieso, A; Gonzalo, N; Fernandez, S; Capote, M L; Vedia, O; Wang, L; Nunez-Gil, I; Grande Ingelmo, J M; Fernandez Rozas, I; Olmos, C; et al.
Abstract: Background: New-onset chest pain occurs in around 20% of patients with long COVID syndrome (LCS). Being the vascular endothelium one of the targets of the SARS-CoV-2 virus, we hypothesized that new onset anginal symptoms in LCS could be due to endothelium dysfunction and other non-obstructive causes of myocardial ischaemia. Methods: We investigated 11 consecutive patients who developed new onset anginal chest pain, suggestive of myocardial ischaemia, after documented SARS-CoV-2 infection. Intracoronary assessment included endothelium-dependent evaluation with acetylcholine testing (Ach), and endothelium-independent assessment with coronary flow reserve (CFR) and microcirculatory resistance (MR). Criteria for positiveness of these tests and medical treatment recommendation were obtained from 2019 ESC guidelines and 2020 EAPCI consensus document on ischaemia with non-obstructive coronary arteries (INOCA). Results: Mean patient age was 56 years (SD ± 15); 10 (91%) were female. In the acute COVID-19 phase, 4 patients (36%) had had pulmonary infiltrates and 2 (18%) required hospitalization. Conclusive non-invasive tests were obtained in 7 (64%), showing exercise-related myocardial ischaemia in 6 (86%). Coronary angiography ruled out obstructive epicardial stenoses in all the patients. Ach testing revealed abnormal endothelium-dependent responses in 9 (82%) patients: 5 (56%) had epicardial vessel and 4 (44%) microvascular spasm. Endothelium-independent assessment was abnormal in 6 (54%) cases, with abnormal CFR in 2 (33%), abnormal MR in 2 (33) and both abnormal CFR and MR in 2 (33%) patients. The most frequent endotype was combined endothelium dependent- and independent abnormalities (6/9, 67%). Stratified medical treatment according to endotype led to significant improvement in Seattle Angina Scores for angina frequency (+22 points, p=0.013) and a notable trend towards angina stability (+25 points, p=0.093) at a mean follow-up time of 222 days. Conclusions: Myocardial ischaemia of non-obstructive origin is common in patients with chest pain and LCS. Vasomotor abnormalities related to endothelial dysfunction occurred in 82% of patients, frequently associated to impaired microvascular vasodilation or high microvascular resistance. Stratified medical treatment led to significant improvement in angina stability and frequency. Funding Acknowledgement: Type of funding sources: None.